Influence of alkali and alkaline earth metals on pyrolysis of palm kernel shell - Kamarul Zaman, Khairunnisa (2021)
Pyrolysis is a promising technology for the production of renewable fuels and chemicals from high-lignin biomass. With the growing interest in utilizing lignin, using cheap and naturally available catalyst such as alkali and alkaline earth metals (AAEM) has becoming more attractive. However, significant knowledge on how it influences the thermochemical reaction during the pyrolysis process is still lacking and questionable. Thus, this study aimed to investigate how the AAEM influences the pyrolysis of palm kernel shell (PKS), a biomass feedstock with high lignin content which is vastly available in Malaysia. The untreated, treated and salt impregnated PKS samples were used in this study. The treated PKS was prepared using mild acetic acid, soaked with solutions at 50°C. The impregnation of AAEM on treated PKS was achieved by using chloride salts of Na, K, Mg and Ca. The research starts with a physicochemical analysis of PKS focusing on the influence of particle size on AAEM concentrations (dpA: <0.3mm, dpB: 0.3-0.7mm, dpC: 0.7-1mm, dpD: 1-2mm). The results show that smaller particle size exhibited higher ash and AAEM content. The second objective is to analyse the thermal degradation of all investigated PKS samples via thermogravimetric analysis (TGA). TGA analysis showed that the char residue at 900°C was the least for PKS sample size (dp) from treated PKS dpD* and untreated PKS dpA (11.3 mass%) while dpB, dpC and dpD had higher char residue (26.3 mass%). Maximum degradation temperature of PKS impregnated with Ca in hemicellulose region reduced from 307 to 248°C while in the presence of K, the temperature reduced from 300 to 276°C. The third objective is to investigate the effect of AAEM on pyrolysis product yield and composition of pyrolysis oil from all types of PKS sample. The result showed that the treated PKS produced the highest oil yield at 500°C (52.4 wt.%) compared to untreated PKS (46.7 wt.%). From composition analysis of pyrolysis oil, the presence of alkali metals promoted the production of catechols and syringols while the presence of alkaline earth metals suppressed the production of catechols, syringols and guaiacols in pyrolysis oil. The fourth aim is to determine the most suitable kinetic method to predict the kinetic parameters for treated PKS samples. By using experimental data from TGA analyzer, three kinetic methods (Reaction rate constant, Doyle’s approximation and Murray and White’s approximation) were evaluated and the method with the least mean squared error value was selected to determine the kinetic parameters of the PKS impregnated with Ca. The results showed that Murray and White’s approximation is the most suitable kinetic method with the least mean squared error less than 0.5. The fifth objective is to correlate the pyrolysis reaction rate with different concentration of Ca in treated PKS. Using kinetic parameters calculated from Murray and White’s approximation and a modified Langmuir Hinshelwood relation, three models were developed based on hemicellulose, cellulose and lignin thermal degradation temperature range. The result showed that hemicellulose and cellulose models were successful in predicting the pyrolysis reaction rate of PKS impregnated with Ca up to 6% for thermal degradation that occurred between 290 and 365°C.